Cassava biotechnology research at CIAT/Colombia - Fregene, Martin A.; Ceballos, H.; Roca, W.; Okogbenin, Emmanuel; Akano, A.; Mba, Chikelu; Chavarriaga Aguirre, Paul; Tohme, Joseph M.; Ospina Patiño, Bernardo (International Center for Tropical Agriculture, 2001)
Cassava is probably the most efficient producer of carbohydrate per unit land area under tropical conditions. The high productivity of cassava makes it an attractive source of renewable industrial raw material, provided ways are found to reduce production costs and solve constraints. Cassava has a long growth cycle, anywhere from 8-24 months, which means that it is visited by many pests that may also transmit diseases. It is vegetatively propagated, and securing sufficient and healthy planting material can be a problem for many small farmers. Biotechnology can contribute to solutions of these problems and realize great benefits for cassava farmers. Since the 1980s CIAT has worked to realize the potential of biotechnology for cassava, especially to solve those problems that can not be dealt with effectively through conventional approaches. Cassava biotechnology research at CIAT falls into three broad areas, namely: genetic transformation, molecular marker development/marker-assisted breeding, and the rapid multiplication of healthy planting material. Genetic transformation projects include the engineering of cassava with the bt gene for resistance to the cassava stem borer (Chilomina clarkei), and other pests susceptible to the bt protein; the production of herbicide resistant cassava, Round-up ready cassava; and the bio-engineering of cassava for the production of novel polymers. The CIAT molecular genetic map of cassava --- the first such map to be constructed entirely at a CGIAR center --- is being applied to dissect complex traits, such as early bulking, and to realize earlier unachievable goals, such as breeding for resistance to the African Cassava Mosaic Disease (ACMD) in Latin America. ACMD is not only the most serious constraint of the crop in sub-Saharan Africa, but is also a potential threat in tropical America and Asia. The whitefly biotype that serves as the virus's vector has already been found in the Caribbean and in Brazil, and it is a matter of time before the virus appears as well. Simple sequence repeat (SSR) markers from the map have also been employed in the characterization of genetic diversity, towards a definition of heterotic patterns in cassava. The rate of spread of a successful variety continues to remain slow. Rapid propagation of cassava, using the continuous media cycling method (RITA), is being tested to provide large quantities of disease-free material to farmers or to commercial producers of planting material. The CIAT cassava biotechnology team also works in partnership with the Latin American and Caribbean Cassava Consortium (CLAYUCA) to apply biotechnology to overcome constraints of cassava, and to make the crop more competitive, both as a source of food and as raw material for animal feed and other industrial uses. Such alliances between the public and private sectors to solve problems of mutual concern, are the best hope for increasing the income of millions of poor producers and consumers through cutting-edge science.